PENGUATAN KOMPETENSI MANAJERIAL GURU PENGGERAK - Rio Nardo; Nur Fitriyani Sahamony; Muhammad Arif Abdul Hakim; Ratnasartika Aprilyani; Susriyanti Susriyanti; Suhelmi Helia; Firdaus Basbeth (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2024)
Strengthening the Managerial Competence of Driver Teachers is an effort to improve the managerial quality of teachers who play a driving role in education. This includes developing skills in leading, managing resources and motivating teams to achieve educational goals. Lead teachers are those who not only teach in the classroom but also lead by example, inspire and motivate their colleagues and involve them in strategic decision-making to improve the quality of education in schools. Strong managerial skills include the ability to plan strategically, organize resources, manage time and priorities, and build and maintain effective working relationships. Strengthening managerial competencies is done through continuous training and development. This includes workshops, courses, mentoring and hands-on experience in complex education project management. In addition to managerial skills, teacher leaders also need to have strong leadership skills. They need to be able to drive the school's vision and mission, motivate staff and build an inclusive and collaborative work culture. Lead teachers are often the catalyst for change in schools. They drive innovation in teaching methods, curriculum development and the implementation of new educational technologies to improve student learning outcomes